Identifying priority sites for the on-farm conservation of landraces and systematic diversity monitoring through an integrated multi-level hotspot analysis: the case of potatoes in Peru - Dawson, T.; Juarez, H.; Maxted, N.; Haan, Stef de (Frontiers Media, 2023)
Introduction: Effective monitoring of the in situ conservation status and change dynamics of landrace populations in their centers of origin ideally requires the identification of sites that are complementary in terms of the richness, uniqueness and coverage of genetic diversity.